A passive self-tuning vibration neutraliser using nonlinear coupling between the degrees of freedom. (15th February 2023) - Nehemy, Gabriella Furlan; Rustighi, Emiliano; Gonçalves, Paulo J. Paupitz; Brennan, Michael J.
Graphical abstract: Highlights: A passive self-tunning vibration neutralizer is described and tested. The neutralizer can tune itself to two different excitation frequencies. Numerical models are developed to describe the neutralizer behavior. Abstract: Vibration neutralisers are widely used to suppress vibration of a host structure subject to external excitation at a specific frequency. When attached to a structure, they create a notch filter in the frequency response, reducing the vibration levels considerably. An inherent limitation is related to the narrow frequency range in which they are effective. Over the years, there have been different attempts to make the vibration absorber more robust. These include using active and semi-active control strategies to change the tuning frequency, using piezoelectric elements with shunt circuits, electromagnetic actuators, servo motors, and even exploring nonlinear effects. In many cases, there is a need for an external power source to modify the characteristics of the system. This paper concerns a passive vibration neutraliser that can adapt automatically to one of two frequencies corresponding to the frequency of an external harmonic force. Importantly, it does this without the need for an external power source. The device consists of a beam-like neutraliser that is attached to the host structure at its centre through a roller bearing. The stiffness element is a rectangular beam that can rotate in the bearing, changing the stiffness it presents to the direction of excitation. The paper describes an experimental study into such a device, and an analytical model is proposed that qualitatively captures the time-domain behaviour of the experimental device. A possible mechanism by which the device self-tunes to either of the two frequencies of excitation is discussed. Supplementary material is also provided to show the device in operation.